1991
DOI: 10.1038/jcbfm.1991.162
|View full text |Cite
|
Sign up to set email alerts
|

The Microglial Reaction in the Rat Dorsal Hippocampus following Transient Forebrain Ischemia

Abstract: We have examined the distribution and time course of the microglial reaction in the rat dorsal hippocampus after 25-min transient forebrain ischemia (four-vessel occlusion model). Microglial cells were visualized in brain sections using lectin staining with the Griffonia simplicifolia B4-isolectin following intervals of reperfusion ranging from 20 min to 4 weeks. Increased staining of microglial cells was detected in the dentate hilus and area CA1 as early as 20 min after reperfusion. These same regions demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
104
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(111 citation statements)
references
References 30 publications
6
104
1
Order By: Relevance
“…There is increasing evidence that microglial cells contribute to delayed neuronal death. Recruitment and activation of microglial cells gradually increase within the hippocampal CA1 area over 24 h after transient forebrain ischemia, before the degeneration of neurons [28]. Endangered neurons can release proinflammatory chemokines such as monocyte chemoattractant protein-1 (MCP-1/CCL2) and secondary lymphoid-tissue chemokine (SLC/CCL21).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that microglial cells contribute to delayed neuronal death. Recruitment and activation of microglial cells gradually increase within the hippocampal CA1 area over 24 h after transient forebrain ischemia, before the degeneration of neurons [28]. Endangered neurons can release proinflammatory chemokines such as monocyte chemoattractant protein-1 (MCP-1/CCL2) and secondary lymphoid-tissue chemokine (SLC/CCL21).…”
Section: Discussionmentioning
confidence: 99%
“…Microglia, immune cells in the CNS, have been reported to proliferate after CNS damage. 4 These proliferated microglia possibly accelerate neuronal damage by releasing toxic substances. [6][7][8] We previously reported that microglial proliferation and activation were observed in the damaged spinal cord, and that the time course of the progress of hind-limb function loss was quite similar to that of the microglia proliferation in spinal cord after a compression injury.…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions such as ischemia 4 and trauma, 5 microglia proliferate and are activated. These pathologically activated microglia accelerate neuronal damage by releasing nitric oxide, superoxide and inflammatory cytokines such as TNF-a.…”
Section: Introductionmentioning
confidence: 99%
“…Post-ischemic inflammation has been suggested to contribute to delayed neuronal damage at the periphery of infarcts (Stoll et al, 1998), implicating microglia as important mediators in ischemic brain damage. Microglia become activated in response to varying severities of ischemia leading to upregulation of major histocompatibility complex (MHC) class I antigen (Morioka et al, 1991) and nitric oxide synthase (NOS; Yamashita et al, 1995). In the latter case, it is suggested that increased NO production by activated microglia may contribute to neuronal death, thus providing a putative link between microglial activation and post-ischemic neuronal damage.…”
Section: Introductionmentioning
confidence: 99%